Changes in the health‐related quality of life of patients with prostate cancer and their spouses. Issue 1 (12th December 2017) - Harju, Eeva; Rantanen, Anja; Kaunonen, Marja; Helminen, Mika; Isotalo, Taina; Åstedt‐Kurki, Päivi
ABSTRACT: The purpose of this study was to determine how the health‐related quality of life (HRQoL) of patients with prostate cancer and their spouses change during the 6 months after diagnosis and which factors explain the changes. Patients with prostate cancer and their spouses have reported a decrease in HRQoL, but simultaneous follow‐up of the HRQoL of patients with prostate cancer and their spouses is rare. The sample consisted of 186 couples. The participants personally filled in the RAND‐36‐Item Health Survey, both at the time of diagnosis and 6 months later. Changes in the HRQoL were analysed statistically using descriptive statistics and non‐parametric tests. Linear regression models were used to identify the factors associated with the changes in HRQoL in the patients and their spouses. The HRQoL of patients with prostate cancer and their spouses did not change significantly during the first 6 months after diagnosis. Changes in the patients' bodily pain and physical functioning were explained by their background variables. The spouses' background variables did not explain the changes in HRQoL during the follow‐up period. In addition, the changes in the HRQoL of patients and their spouses are very similar. There is a need for long‐term assessment of changes in the HRQoL of patients with prostate cancer and their spouses. The findings indicate that attention should be paid to spouses with regard to the nursing of patients with prostate cancer, as spouses seem to be an important resource for patients with prostate cancer.